2020
DOI: 10.1007/s00259-020-04929-1
|View full text |Cite|
|
Sign up to set email alerts
|

End-to-end automatic differentiation of the coronavirus disease 2019 (COVID-19) from viral pneumonia based on chest CT

Abstract: Purpose In the absence of a virus nucleic acid real-time reverse transcriptase-polymerase chain reaction (RT-PCR) test and experienced radiologists, clinical diagnosis is challenging for viral pneumonia with clinical symptoms and CT signs similar to that of coronavirus disease 2019 (COVID-19). We developed an end-to-end automatic differentiation method based on CT images to identify COVID-19 pneumonia patients in real time. Methods From January 18 to February 23, 2020, we conducted a retrospective study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 24 publications
0
70
0
3
Order By: Relevance
“…Notably, clinical diagnosis should by no means solely base on algorithmic predictions. DL models combining CT and clinical features start to match [13] or surpass [31] performance of senior radiologists in detecting COVID-19, but the road toward clinical application is long and difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, clinical diagnosis should by no means solely base on algorithmic predictions. DL models combining CT and clinical features start to match [13] or surpass [31] performance of senior radiologists in detecting COVID-19, but the road toward clinical application is long and difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrated that radiologists' performance improves upon consultation of AI: Junior radiologists along with AI can perform as well as mid-senior radiologist [30] and radiologists' sensitivity and specificity can improve by nearly 10% through AI [31]. Similarly, in a blind review with six radiologists' decisions with AI support were superior to radiologists alone (sensitivity 88% vs. 79%, specificity 91% vs. 88%), although the AI model alone performed the best (95% and 96%) [32].…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…It was confirmed by the two experienced radiologists from the Youan Hospital that no lesion areas of COVID-19, pneumonia, or influenza were present in the 120 cases. We also collected the CT-data of pneumonia cases from a public data set (images of COVID-19 positive and negative pneumonia patients: ICNP) 56 . The CT-data collected from the Youan hospital contained 95 patients diagnosed with COVID-19, 50 patients diagnosed with influenza and 215 patients diagnosed with pneumonia.…”
Section: Methodsmentioning
confidence: 99%
“…In each stage, the lower lobes were more inclined giving raise to CT scores and the highest CT score was obtained in 10 days after the onset of initial symptoms [155]. Song et al [156] developed an automatic differentiation method for the real-time identification of COVIDS-19 infection based on the CT scan. The sensitivity and specificity obtained through this analysis from CT image were 92% and 91%, respectively.…”
Section: Currently Emerging Clinical Diagnosismentioning
confidence: 99%